Inclusive Education: Challenges and Opportunities - Shahzada Akhter; Monika Chibb; Dr. Najmah Peerzada (International Journal of Indian Psychȯlogy, 2022)
A modern strategy for schooling children who have learning difficulties and disabilities alongside usually growing kids under one roof is known as inclusive education. It attempts to support every student in realising their full potential by bringing them together in one classroom, irrespective of their weaknesses and strengths. Providing equal access to education for all students is the main challenge facing educational institutions worldwide, both in industrialised and poor nations. Children with impairments have significantly more frequently enrolled in schools during the last twenty years for a variety of reasons, including favourable laws and the expanded availability of aids and appliances, among others. Yet, there hasn’t been much focus on the effectiveness of the education and learning that children with disabilities receive. Still the primary concern is on assimilation into a mainstream system, which is filled with many challenges. The inclusive education includes transforming the environment of the conventional educational system with focus on action learning, practical curriculum, appropriate evaluation techniques, multilevel teaching approaches, and improved attention to varied student needs. This paper concerns with challenges and opportunities in efforts towards country’s inclusive education.